2015
DOI: 10.1002/2327-6924.12201
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a postdischarge coronary artery disease management program

Abstract: Objectives We conducted a demonstration project to assess the value of a nurse practitioner (NP) based coronary artery disease management (CAD‐DM) program for patients with an acute coronary syndrome (ACS) or percutaneous coronary intervention. Methods Patients were recruited to attend three 1‐h monthly visits. The intervention included assessment of clinical symptoms and guideline‐based treatments; education regarding CAD/ACS; review of nutrition, exercise, and appropriate referrals; and recognition of signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For this reason, many chronic disease prevention and management (CDPM) programs have been designed with the aim of improving outcomes in these patients. CDPM programs targeting diabetes, [3][4][5][6][7] asthma, 8,9 heart diseases, [10][11][12] depression, [13][14][15] chronic obstructive lung disease (COPD), 16,17 obesity, 18,19 kidney disease, 20 dyslipidemia, 21 hypertension 22 and chronic pain 23 have been shown to be effective in improving outcomes such as hospital admissions, costs, adherence to medication, disease control, use of health services, quality of life and mortality. However, these studies were conducted in different settings and were based on single diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, many chronic disease prevention and management (CDPM) programs have been designed with the aim of improving outcomes in these patients. CDPM programs targeting diabetes, [3][4][5][6][7] asthma, 8,9 heart diseases, [10][11][12] depression, [13][14][15] chronic obstructive lung disease (COPD), 16,17 obesity, 18,19 kidney disease, 20 dyslipidemia, 21 hypertension 22 and chronic pain 23 have been shown to be effective in improving outcomes such as hospital admissions, costs, adherence to medication, disease control, use of health services, quality of life and mortality. However, these studies were conducted in different settings and were based on single diseases.…”
mentioning
confidence: 99%
“…For this reason, many chronic disease prevention and management (CDPM) programs have been designed with the aim of improving outcomes in these patients. CDPM programs targeting diabetes, 3-7 asthma, 8,9 heart diseases, [10][11][12] costs, adherence to medication, disease control, use of health services, quality of life and mortality. However, these studies were conducted in different settings and were based on single diseases.…”
mentioning
confidence: 99%
“…In 2014, the National Directors of Public Health Nursing 23 reiterated the need to develop clinical nurse specialist (CNS) and advanced nurse practitioner (ANP) roles within primary care reform for delivery of chronic disease management programmes. Despite these recommendations plus research evidence indicating the effectiveness of nurse-led multidisciplinary CVD programmes in primary care, 24 this study provides empirical testimony that no such role developments have yet transpired for CVD. The vital role of the nurse in CVD prevention is increasingly endorsed in the literature 25 and also in the recent ESC guidelines.…”
Section: Expansion Within the Phn Rolementioning
confidence: 84%
“…These included biometric and biochemical data to measure response to treatment, as well as self-reports of symptom improvement and health related quality of life. For example, individuals with diabetes generally experienced reduced HbA1cs (Chang, Davis et al 2007, Stone, MacPherson et al 2010, Choi and Rush 2012, Jessee and Rutledge 2012 while other individuals reported an improvement in symptoms specific to their disease process (Philp, Lucock et al 2006, Wright, Purdy et al 2007, Owens, Eby et al 2012, Sawatzky, Christie et al 2013, Voorn, Vermeulen et al 2013, Housholder-Hughes, Ranella et al 2015, Kozlowski, Lusk et al 2015, Teunissen, Stegeman et al 2015. In some studies caregivers also benefitted from the nurse practitioner intervention, such as caregivers of patients with dementia who reported a reduced caregiver burden (Ament, Wolfs et al 2015).…”
Section: Individual Benefitsmentioning
confidence: 99%